Building an Inclusive Culture in the Chemistry Department at Imperial College. Issue 11 (11th February 2016) - Welton, Tom
Abstract : One of the main aims of any department is to appoint the very best chemists and to support them to reach their full potential. Success in this aim cannot look like a male to female ratio of professors of 20:1. In this Guest Editorial, T. Welton, Dean of the Faculty of Natural Sciences at Imperial College London, describes the processes introduced that led to the Chemistry Department at Imperial achieving a gold Athena SWAN award.